DARI LITERASI SUNGAI KE KOMUNIKASI RISIKO: STRATEGI MEDIA RELATIONS KOMUNITAS BACA CILIWUNG DALAM MEMBANGUN KETAHANAN BANJIR BERBASIS KOMUNITAS [FROM RIVER LITERACY TO RISK COMMUNICATION: MEDIA RELATIONS STRATEGIES OF KOMUNITAS BACA CILIWUNG IN BUILDING COMMUNITY-BASED FLOOD RESILIENCE] - Kristiani, Anastasia Putri; Natalia, Desi; Rohman, Asep Abdul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Flood disasters remain a recurring challenge in Indonesia, driven by climate change, rapid urbanization, and the degradation of river ecosystems. In this context, effective risk communication is essential to enhance community preparedness and resilience. This study examines how media relations strategies implemented by Komunitas Baca Ciliwung transform river literacy into actionable disaster risk communication. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and media content analysis. The findings indicate that media relations extend beyond information dissemination to function as a tool for community empowerment. The community applies multidimensional strategies, including digital media utilization, collaboration with mass media, and locally grounded storytelling to communicate flood risks effectively. These approaches enable the translation of environmental literacy into contextual messages that are easily understood and adopted by local communities. Furthermore, trust and cultural proximity play a critical role in enhancing communication effectiveness. Community-based media relations foster participatory engagement, strengthen public trust, and encourage adaptive behaviors toward flood risk mitigation. Despite challenges such as misinformation and unequal digital access, this study demonstrates that community-driven communication models significantly contribute to building sustainable flood resilience.